Application of Complaint Handling by Approach Model of ISO 10002 : 2004 to Increase Complaint Services - Agus Sukoco; Yuthsi Aprilinda (Bandar Lampung University (UBL), 2013)
This study describes the components of available forage in Vahregan watershed, Central Iran and highlight issues relating to forage endowment and environmental dynamics. In this study, proper use factor and palatability models and their components use to develop the model of available forage and measure it. The components climatic, topography, land systems, vegetation, land use and grass and shrub species composition changes were analyzed using GIS. In this study source of information are herders, land and livestock owners, research institution and personal field inspections. Responses to the questionnaires were obtained from local government offices and research on rangelands and analyzed in parallel with the results of detailed interviews with pastoralists. The results of the completed overall model of available forage showed that of the 18346.2 hectares in the range area only 8.36% of the rangeland is in good condition and the rest are in fair (13.8%), poor and very poor (77.82%). About 16812.85 ha (91.64%) of the rangeland area shows a downward trend, only 1533.35 ha (8.36%) upward trend. About half of the rangeland is not favorable for domestic livestock grazing. The range condition situation and its trend in consideration of soil and slope properties in this study indicates that the rangeland in Vahregan is a fragile production system, sensitive to soil erosion and rangeland degradation, so for a long time sustainable exploitation should be goes to minimize land degradation in the future, proper management and sustainable exploitation should be implemented in the future